A novel cause of chronic viral meningoencephalitis: Cache Valley virus. Issue 1 (July 2017) - Wilson, Michael R.; Suan, Dan; Duggins, Andrew; Schubert, Ryan D.; Khan, Lillian M.; Sample, Hannah A.; Zorn, Kelsey C.; Rodrigues Hoffman, Aline; Blick, Anna; Shingde, Meena; DeRisi, Joseph L.
Abstract : Objective: Immunodeficient patients are particularly vulnerable to neuroinvasive infections that can be challenging to diagnose. Metagenomic next generation sequencing can identify unusual or novel microbes and is therefore well suited for investigating the etiology of chronic meningoencephalitis in immunodeficient patients. Methods: We present the case of a 34‐year‐old man with X‐linked agammaglobulinemia from Australia suffering from 3 years of meningoencephalitis that defied an etiologic diagnosis despite extensive conventional testing, including a brain biopsy. Metagenomic next generation sequencing of his cerebrospinal fluid and brain biopsy tissue was performed to identify a causative pathogen. Results: Sequences aligning to multiple Cache Valley virus genes were identified via metagenomic next generation sequencing. Reverse transcription polymerase chain reaction and immunohistochemistry subsequently confirmed the presence of Cache Valley virus in the brain biopsy tissue. Interpretation: Cache Valley virus, a mosquito‐borne orthobunyavirus, has only been identified in 3 immunocompetent North American patients with acute neuroinvasive disease. The reported severity ranges from a self‐limiting meningitis to a rapidly fatal meningoencephalitis with multiorgan failure. The virus has never been known to cause a chronic systemic or neurologic infection in humans. Cache Valley virus has also never previously been detected on the Australian continent. Our research subject traveled to North and South Carolina and Michigan in the weeks prior to the onset of his illness. This report demonstrates that metagenomic next generation sequencing allows for unbiased pathogen identification, the early detection of emerging viruses as they spread to new locales, and the discovery of novel disease phenotypes. Ann Neurol 2017;82:105–114